DESIGN, FORMULATION, AND CHARACTERIZATION OF APREMILAST – SACCHARIN COCRYSTALS LOADED WITH TOPICAL GEL - MANE, TEJASWINI; MOHITE, MUKESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Most of the drugs are relevant BSC class II and class IV having solubility problem. Co-crystallization of drug with coformer is an immense approach used to explore the physicochemical properties of drug. The objective of the present work was to design formulate and evaluate the drug cocrystals of poorly soluble drug apremilast (APR) with saccharin. Methods: Cocrystals of APR were prepared using a solvent evaporation technique. The saturated solubility study and in vitro dissolution study of cocrystals were carried out. The prepared cocrystals were characterized by differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The topical gel of APR cocrystals was formulated optimized and evaluated using 3-level factorial design. Results: The cocrystals of APR were prepared in 1:1 molar ratio with saccharin. APR cocrystals showed the improvement in solubility and dissolution as compared to pure APR. The formation of cocrystals was confirmed from a change in the endothermic peak of DSC and from shifting of FTIR spectra of cocrystals. Crystallinity of cocrystal was confirmed from XRD pattern and noteworthy change in 2θ values of the intense peak. The topical gel of APR cocrystals was formulated and optimized using 3-level factorial design using Carbapol-940 and hydroxypropyl methylcellulose as a gelling agent. Conclusion: The cocrystals with altered physicochemical properties of APR was prepared with saccharin and formulated as a topical gel to overcome the problems related to oral administration.